2020
DOI: 10.4103/ijmpo.ijmpo_6_20
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of services to childhood cancer survivors in India: A national survey

Abstract: Background: Continuum of care is an important concern for childhood cancer survivors. Studies from high-income countries indicate a significant development in services to these survivors. Similar information is unavailable from India. Methods: An online survey form was developed and sent to 86 centers. Data were collected over a 6-month period in 2017. Results: Fifty nine centers responded (44.1% private sector, 33.9% public, and 22.0% charitable trust). The services are mainly provided (91%) within routine on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 14 publications
(15 reference statements)
1
16
0
Order By: Relevance
“…2,15 A recent audit at our clinic found that the major causes for attrition to follow-up include gaps in awareness, financial toxicity, and "social stigma," similar to results of a nationwide survey. 12,16 At registration into the ACT Clinic, the gender ratio of 2.5:1 (male preponderant), while skewed, was similar to that at initial cancer diagnosis at our center. However, several female survivors discontinue clinic visits into adulthood and marriage.…”
Section: The Need To Recognize the Unique Spectrum Of Late Effects In...mentioning
confidence: 57%
See 2 more Smart Citations
“…2,15 A recent audit at our clinic found that the major causes for attrition to follow-up include gaps in awareness, financial toxicity, and "social stigma," similar to results of a nationwide survey. 12,16 At registration into the ACT Clinic, the gender ratio of 2.5:1 (male preponderant), while skewed, was similar to that at initial cancer diagnosis at our center. However, several female survivors discontinue clinic visits into adulthood and marriage.…”
Section: The Need To Recognize the Unique Spectrum Of Late Effects In...mentioning
confidence: 57%
“…7 However, a national survey to assess delivery of services to CCS found poor availability of extended service providers such as endocrinologists and psychologists. 12 Transitioning from Acute Care to Survivorship Care: Catch them Early, and Catch them Young One of the major challenges that we have faced is to streamline and increase recruitment to the ACT Clinic in our highvolume center. Children who complete treatment are followed up in the routine outpatient department until they are eligible to enroll in the ACT Clinic, that is, 5 years from start of treatment and 2 years from completion of treatment.…”
Section: The Need To Recognize the Unique Spectrum Of Late Effects In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Such collaborations with nonprofit organizations are perceived to represent a means to extend access to survivorship care in centers with limited or no special services and resources, which represents a large portion of pediatric cancer centers in India. 36 …”
Section: Resultsmentioning
confidence: 99%
“… 12 International studies on medical undergraduates and oncology fellows have reported a lack of knowledge and a high prevalence of misconceptions regarding key cancer survivorship issues. 13 However, most healthcare providers expressed interest in knowing more, and small interventions in education have been shown to bring objective success. 14 Greater confidence in the primary care providers’ abilities to address issues faced by CCS is believed to be a significant facilitator for those survivors seeking care for health issues that emerge.…”
Section: Introductionmentioning
confidence: 99%